2009
DOI: 10.1063/1.3278594
|View full text |Cite
|
Sign up to set email alerts
|

Two-color quantum dot laser with tunable wavelength gap

Abstract: We report on two-color InAs/InP(100) quantum dot lasers with tunable wavelength gap. Two peaks of lasing emission were observed simultaneously, while the high energy peak undergoes continuous blueshift with the increase in the injection current, and the low energy peak is somewhat fixed. Sophisticated studies of the wavelength gap as a function of the laser power prove that the two-peak lasing and shifting is not caused by the effect of Rabi oscillation. Moreover, comparison of electroluminescence and lasing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…4(b). This is possible in a highly inhomogeneous system due to change in carrier distribution among the Qdash stacks (caused by carrier spill-over) which affects the gain profile, and hence the emission spectra [21], [28].…”
Section: A Ridge-waveguide Lasersmentioning
confidence: 99%
“…4(b). This is possible in a highly inhomogeneous system due to change in carrier distribution among the Qdash stacks (caused by carrier spill-over) which affects the gain profile, and hence the emission spectra [21], [28].…”
Section: A Ridge-waveguide Lasersmentioning
confidence: 99%
“…Temperature has a great impact on carriers' distribution in QD, which leads the laser to exhibit a special lasing process. At room temperature, we simultaneously observed a two-color emission from a monolithic chip of the InAs/InP QD laser and demonstrated that the two peaks of the lasing emission with a tunable wavelength gap were not caused by the effect of the Rabi oscillation [11] . We further studied the lasing characteristics of the same QD laser at a low temperature.…”
mentioning
confidence: 82%
“…The special features from the QD laser are naturally expected from their unique quantum structure providing extreme confinement for carriers, which results in multiple colors emitting simultaneously from a monolithic chip. Recently, at room temperature, a two-color emission from a monolithic chip of InAs/InP QD laser was reported as a result of the increase of an injection current [10,11] . The operation temperature was found to have an important effect on the performance of the two-color QD laser.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In QD-MLLs the lowest pulse widths are typically found at low injection currents just above laser threshold. The pulses tend to broaden when gain current is increased [43][44][45]. In order to ensure low pulse width and high average power, the presence of CW-ES emission proved to have a beneficial effect on the GS ML.…”
Section: Pulse Width Narrowing Due To Gs Splittingmentioning
confidence: 99%